Allosteric interactions prime androgen receptor dimerization and activation - Elizabeth V. Wasmuth; Arnaud Vanden Broeck; Justin LaClair; Elizabeth A. Hoover; Kayla E. Lawrence; Navid Paknejad; Kyrie Pappas; Doreen Matthies; Biran Wang; Weiran Feng; Philip A. Watson; John C. Zinder; et al. (2022)
The androgen receptor (AR) is a nuclear receptor that governs gene expression programs required for prostate development and male phenotype maintenance. Advanced prostate cancers display AR hyperactivation and transcriptome expansion, in part, through AR amplification and interaction with oncoprotein cofactors. Despite its biological importance, how AR domains and cofactors cooperate to bind DNA has remained elusive. Using single-particle cryo-electron microscopy, we isolated three conformations of AR bound to DNA, showing that AR forms a non-obligate dimer, with the buried dimer interface utilized by ancestral steroid receptors repurposed to facilitate cooperative DNA binding. We identify novel allosteric surfaces which are compromised in androgen insensitivity syndrome and reinforced by AR's oncoprotein cofactor, ERG, and by DNA-binding motifs. Finally, we present evidence that this plastic dimer interface may have been adopted for transactivation at the expense of DNA binding. Our work highlights how fine-tuning AR's cooperative interactions translate to consequences in development and disease.